2015
DOI: 10.1038/pr.2015.45
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine reduces cranial temperature in hypothermic neonatal rats

Abstract: Background:The α2-adrenergic agonist dexmedetomidine (DEX) is increasingly used for prolonged sedation of critically ill neonates, but there are currently no data evaluating possible consequences of prolonged neonatal DEX exposure. We evaluated the pharmacokinetics and histological consequences of neonatal DEX exposure. Methods: DEX was administered (s.c.) to naive (uninjured) neonatal Lewis rats to provide acute (25 µg/kg, ×1) or prolonged (25 µg/kg three times daily, ×2 or ×4 d) exposure. Therapeutic hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
1
8
1
Order By: Relevance
“…Dex is an α-2A adrenergic receptor agonist commonly administered to patients as a sedative and analgesic (29). Previous studies have reported Dex to be neuroprotective when combined with hypothermia (30,31). However, few studies have assessed the association between Dex and hypothermia, making the mechanism of this process unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Dex is an α-2A adrenergic receptor agonist commonly administered to patients as a sedative and analgesic (29). Previous studies have reported Dex to be neuroprotective when combined with hypothermia (30,31). However, few studies have assessed the association between Dex and hypothermia, making the mechanism of this process unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of acute (25 μg/kg) or prolonged (25 μg/ kg 3 times daily for 2 or 4 days) exposure of dexmedetomidine with TH on uninjured neonatal Lewis rats was studied [59] . Prolonged dexmedetomidine treatment in neonatal rats was not associated with abnormal brain histology (there was no increased gliosis, macrophage activation, or apoptosis in either the hypothermic or control rats).…”
Section: Discussionmentioning
confidence: 99%
“…In our model, prolonged sedation of mechanically-ventilated HIE animals was feasible using either morphine or DEX, an α2-adrenergic receptor agonist that is often used in neonatal intensive care units for sedation and pain management [28,29]. While sedation with DEX may be beneficial for neonates with HIE based on animal models [3032], PK data in the setting of HIE are lacking.…”
Section: Discussionmentioning
confidence: 99%